Competence of The Court In Adjudicating Corruption Cases Committed By Officials Based On Discretionary Authority - Widhartama, I Gede; Salmon, Hendrik; Mustamu, Julista (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Discretion As freedom of acting or making decisions from authorized and authorized state administration officials in their own opinion in government practices, the use of discretion should not be worried about by government officials. Aside from being a principle in carrying out government functions, discretion also has a strong legal basis based on the Government Administration Law that concerns the policy not a few that are processed and charged with the Corruption Criminal Act, so that officials are trapped as corruptors because of their duties attached to positions That. But that does not mean that the judge is free to make a decision. Ethics and morals are the commonly known judges. In Indonesia, maybe what is meant is the code of ethics and guidelines for judges produced by the Supreme Court and the Judicial Commission. So as to minimize the use of wrong discretion authority which results in the problem of criminal acts of corruption. Purposes of the Research: This writing aims to find out the legitimacy of establishing a new high court in the islands. Methods of the Research: The research used by the author is a normative juridical research type. The procedure for collecting legal materials is carried out by conducting library research on legal materials, namely primary, secondary and tertiary legal materials. Then the legal material that has been obtained is analyzed qualitatively. Results of the Research: The results obtained are the Legitimacy of the Formation of a New High Prosecutor's Office in the Islands, to minimize the obstacles faced by the islands in fighting for people's rights.